Legal limitations in the practice of the primary health care nurse - J. Bierman; M. Muller (AOSIS, 1994)
In this article the legal limitations in the practice of the primary health care nurse in the Republic of South Africa, having direct implications for the achievement of the goal: "Health for all by the year 2000", are explored and described The questions which had to be answered by means of the research are in relation to the nature and scope of the limitations obstructing the practice of the primary health care nurse. A legislative (document) analysis was performed and limitations in the legislation confirmed. It is recommended that an empirical investigation be done to verify the results after which amendments and clarification of the legislation may be requested.